A day in the life of older people in a rehabilitation setting: an observational study. (June 2015) - McKillop, Ann; Parsons, John; Slark, Julia; Duncan, Lindsay; Miskelly, Philippa; Parsons, Matthew
Abstract Purpose: Nurses' contribution during inpatient rehabilitation is well documented. However, despite being the largest professional group in this setting, the specialty of rehabilitation nursing is poorly recognised. This article reports on the first of a four-phase study that aimed to clarify and develop the nursing contribution to inpatient rehabilitation for older persons. The aim of this study was to identify activity patterns and time use during daytime and evenings of older adult patients undergoing inpatient rehabilitation. Methods: Direct observation using behavioural modelling was undertaken of a convenience sample of 37 older people undergoing inpatient rehabilitation in a specialist unit of a large tertiary hospital in New Zealand. The primary outcome was the observation of meaningful activity. Binomial logistic regression was used to study the association between relevant variables. Findings: Meaningful activity was most likely to involve walking without assistance and to occur 08:00 to 14:00 h and 16:00 to 21:00 h during weekdays. Patients were more likely to receive treatment during the weekend. Irrespective of time, registered nurses were the health professionals most often present with patients. Conclusions: There is likely to be unrealised opportunities for registered nurses to support improved rehabilitation outcomes. Registered nurses' involvement in rehabilitation needs to be actively optimised. Implications for Rehabilitation Nurses' engagement with older adults in rehabilitation settings is likely to be substantial, placing them as key members of the rehabilitation team. Nurses make a pivotal contribution to inpatient rehabilitation based on specialised knowledge and skills but this contribution is not well understood. Opportunities are likely, at times when allied health professionals are less often present, e.g. evenings and weekends, for registered nurses to more intentionally overlap rehabilitation activities with other care requirements.